Composition of lipid nanoparticles for targeted delivery: application to mRNA therapeutics - Vasileva, Olga; Zaborova, Olga; Shmykov, Bogdan; Ivanov, Roman; Reshetnikov, Vasiliy (Frontiers in Pharmacology, 2024)
Today, lipid nanoparticles (LNPs) are some of the main delivery systems for mRNA-based therapeutics. The scope of LNP applications in terms of RNA is not limited to antiviral vaccines but encompasses anticancer drugs and therapeutics for genetic (including rare) diseases. Such widespread use implies high customizability of targeted delivery of LNPs to specific organs and tissues. This review addresses vector-free options for targeted delivery of LNPs, namely the influence of lipid composition of these nanoparticles on their biodistribution. In the review, experimental studies are examined that are focused on the biodistribution of mRNA or of the encoded protein after mRNA administration via LNPs in mammals. We also performed a comprehensive analysis of individual lipids' functional groups that ensure biodistribution to desired organs. These data will allow us to outline prospects for further optimization of lipid compositions of nanoparticles for targeted delivery of mRNA therapeutics.